β-Cyclodextrin catalyzed synthesis of substituted indoles in aqueous medium - Shankar, Jilla; Satish, Gaddam; Kumar, Bandam Santosh Pavan Anil; Nageswar, Yadavalli Venkata Durga (European Journal of Chemistry, 2014)
β-Cyclodextrin catalyzed synthesis of indole derivatives from indole, aldehyde and N-methylaniline is reported. The β-cyclodextrin can be recovered and reused without significant loss of catalytic activity, and it is inexpensive, readily available when compared to other cyclodextrins (α, γ).